Editorial [Hot Topic: Anticancer Macromolecular Prodrugs in Clinical Trials - an Update (Guest Editor: Felix Kratz)] - Kratz, Felix (Current Bioactive Compounds, 2011)
PROLOGUE Coupling of low-molecular weight anticancer drugs to synthetic polymers or serum proteins through a cleavable linker has been an effective method for improving their therapeutic index through active and targeting approaches and convincing proofof- concepts have been obtained preclinically for a substantial number of prodrug candidates [1]. Drug conjugates with synthetic polymers or serum proteins that have undergone clinical assessment have used clinically established agents such as doxorubicin, camptothecin, paclitaxel, methotrexate and platinum(II) complexes. In 2007, we reviewed those carrier-linked prodrugs that had or were undergoing clinical trials [2]. Meanwhile several clinical trials with carrier-linked prodrugs have been discontinued but other candidates have moved into to the clinical setting or advanced to later stages of clinical trials. Thus, I believe that an update of ongoing clinical trials with macromolecular prodrugs in cancer therapy would prove to be a timely resource for interested parties in this particular field of drug delivery. Seven macromolecular prodrugs are currently in clinical development (see Table 1) that are based on passive tumor targeting. Clinical phase I or phase II studies with N-(2-hydroxypropyl)acrylamide (HPMA) copolymer conjugates with doxorubicin (PK1 and PK2) as well as with camptothecin (MAG-CPT, PNU166148) and with paclitaxel (PNU166945) have not been continued (for a review of these clinical trials see [2]). OPAXIO™ (paclitaxel poliglumex, CT-2103; formerly known as XYOTAX™) is a biodegradable polyglutamate conjugate of paclitaxel that has shown improved efficacy in phase III studies in non-small cell lung cancer patients over paclitaxel, but only in a subpopulation of women with low estrogen levels and phase III studies will be repeated in defined patients with non small lung cancer, but their status will not be reviewed in this edition (see http://www.celltherapeutics.com/opaxio) and Singer et al.: Biological and clinical characterization of paclitaxel poliglumex (PPX, CT-2103), a macromolecular polymer-drug conjugate. Int. J. Nanomedicine, 2006, 1, 375-383. Review). A DACH platinum HPMA complex (AP5436) is the only drug conjugate with a HPMA copolymer that is still being pursued in phase II clinical trials (see article by David P Nowotnik). The clinical development of Pegamotecan, a 4-arm PEG conjugate with camptothecin (CPT) developed by Enzon, Inc. has been replaced by EZN-2208, an analogously constructed PEG conjugate with an active metabolite of camptothecin SN38 (see article by Hong Zhao). The clinical development of two other camptothecin polymer conjugates, DE-310, a carboxymethyldextran conjugate with a CPT analogue (exatecan), and PG-Gly-CPT (CT-2106), in which the 20-HO-position of CPT was bound directly to the carboxylic acid groups of polyglutamate have been stopped or put on hold. Two novel camptothecin polymer conjugates, however, IT-101 and XMT-1001 are meanwhile in clinical development (see articles by Cissy Young et al. as well as Robert J Fram and Alex Yurkovetskiy). A further prodrug of a camptothecin, NKTR-102, a 4-arm pegylated form of irinotecan by Netktar, Inc. is under phase II clinical studies against colon and ovarian cancer and recently showed encouraging response data in platinum refractory ovarian cancer patients (J. Clin. Oncol., 28, 7S - suppl. Abstr. 5013, ASCO2010), but appears to act as a low-molecular-weight prodrug with improved pharmacokinetics and will not be discussed in this edition (see http://www.nektar.com/product_pipeline for further details on this technology)....
Keywords: cancer chemotherapy